Murder at Ochre Court [large type] - Maxwell, Alyssa (Maxwell, Alyssa. Gilded Newport mystery., 2018)
"In the summer of 1898, reporter Emma Cross investigates the shocking death of a debutante at her coming-out ball among the bright lights of Newport's high society"--